2017
DOI: 10.2337/dc16-2001
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance Predicts Cognitive Decline: An 11-Year Follow-up of a Nationally Representative Adult Population Sample

Abstract: Our results show that higher serum fasting insulin and insulin resistance predict poorer verbal fluency and a steeper decline in verbal fluency during 11 years in a representative sample of an adult population. Prevention and treatment of insulin resistance might help reduce cognitive decline later in life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
95
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(98 citation statements)
references
References 36 publications
3
95
0
Order By: Relevance
“…Serum triglycerides, total cholesterol, high‐density lipoprotein (HDL) cholesterol, low‐density lipoprotein (LDL) cholesterol, apolipoprotein B, glucose, insulin, glycated hemoglobin, and C‐reactive protein were all directly measured in an at least 4 hours (50% > 8 hours) fasting state. The biochemical methods are described in detail elsewhere …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum triglycerides, total cholesterol, high‐density lipoprotein (HDL) cholesterol, low‐density lipoprotein (LDL) cholesterol, apolipoprotein B, glucose, insulin, glycated hemoglobin, and C‐reactive protein were all directly measured in an at least 4 hours (50% > 8 hours) fasting state. The biochemical methods are described in detail elsewhere …”
Section: Methodsmentioning
confidence: 99%
“…The biochemical methods are described in detail elsewhere. (24) Follow-up data for hospitalizations were obtained from the National Hospital Discharge Register, which covers all hospitalizations in Finland beginning in 1969. Data for cancers were obtained from the Finnish Cancer Registry, and vital status and cause of death data were obtained from Statistics Finland, which systematically collects data about the deaths of all Finnish citizens.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, characteristics related to type 2 diabetes, including higher blood glucose levels, higher serum fasting insulin and insulin resistance [12][13][14], have been linked to cognitive dysfunction, accelerated cognitive decline and dementia in elderly individuals, even in those without diabetes [14,15]. Moreover, in addition to blood glucose and HbA 1c levels, poor long-term HbA 1c trajectories [16] and glucose peaks [17] have been shown to be associated with cognitive function.…”
Section: Type 2 Diabetes Precedes Cognitive Dysfunctionmentioning
confidence: 99%
“…The estimated parameters for the association of studied predictors and the outcomes in the study conducted by Ekblad et al (1) have been degraded by collinearity among the predictors. As expected, HOMA-IR, glucose, and insulin are highly correlated, so including all of them in the same model resulted in inflation of standard error of the regression coefficients and imprecisely estimated the association of HOMA-IR, glucose, and insulin with cognitive decline.…”
mentioning
confidence: 94%
“…We have read with great interest the article by Ekblad et al (1). The authors showed that in multivariable analysis insulin resistance (IR) and higher levels of insulin can be independent predictors of poorer verbal fluency performance and of a greater decline in verbal fluency during 11 years after adjusting for age, sex, and education (1).…”
mentioning
confidence: 99%